Systematic review: emotional brands from perspective based on advertising - Castro Analuiza, Juan C.; Pazmiño Chimbana, Victoria Micaela (Cuadernos de Administración, 2023)
As a strategic component of advertising, the following study provides valuable feedback based on emotional perceptions of brands. It entails determining whether there is a difference in the core emotions conveyed by soft drink, cosmetic, and technology brands. It was conducted using a systematic review and meta-analysis, as well as the NCSS 12 Data Windows software, the correlated proportions approach, and random sampling. It enabled the generation of Q Cochran’s results as well as a Forest Plot graph displaying the point estimates, intervals, and potential of the selected research. Following the review, it became evident that compared to the technology brand, which had heterogeneity, soft drink and cosmetic brands demonstrated great participation and homogeneity. The most significant feelings for an advertisement were happiness and sadness. As a result, emotional brands with advertising strategies enable consumers to form positive and emotional links such as satisfaction, affection, passion, pleasure, and happiness. With this advertising strategy, the brand has gained consumer awareness, dedication, and genuine loyalty.